Penggunaan Bahasa Pemrograman Python Untuk Menganalisis Faktor Risiko Penyakit Diabetes Pada Masyarakat Keturunan Pima Indian - Gandha, Steve Aditya; Nurhan, Yonathan Immanuel; William, Jeffrey (Journal of Student Development Information System (JoSDIS), 2022)
Diabetes is a disease that has existed for a long time. Until now, the prevalence of this disease is still quite high. Diabetes can occur in people of all ages, both children and adults. There are several factors that can increase the risk of diabetes either from genetic factors, diet, or age. In this study the authors will analyze these factors to see which factors have a strong correlation with diabetes. The analysis will be carried out using the Python programming language with the EDA (exploratory data analysis) method where the data will go through several stages starting from data collection, cleaning, to analysis. Analysis will be assisted by several libraries such as pandas, seaborn, & matplotlib. Data will be presented in tabular form and also in diagram form. In this study the author will also discuss the results of the python code. From this study it was found that things such as body weight, number of pregnancies, and the amount of glucose have a fairly high correlation with the risk of diabetes. Factors that are not natural factors can be prevented/maintained by doing a number of things such as exercising, maintaining food, etc.